Становлення та розвиток органів місцевого самоврядування в Україні (1991–2019 роки) - Загуменна, Ю. О.; Zagumenna, Yu. O.; Лазарєв, В. В.; Lazariev, V. V.; Юлія Загуменна; Лазарєв Віктор Вікторович (Право і безпека. - 2020. - № 77(2). - С. 106-117, 2020)
Досліджено актуальні теоретико-методологічні, нормативно-правові та практичні аспекти діяльності органів місцевого самоврядування в Україні; розглянуто історичні закономірності його формування та розвитку (1991–2019 роки). Визначено етапи реформування місцевого самоврядування і територіальної організації публічної влади в Україні. Розглянуто актуальні проблеми забезпечення ефективного функціонування органів місцевого самоврядування.

Local self-government is an integral part of a democratic society, since it actively influences the political and socioeconomic conditions for the development of civil society, and becomes an important prerequisite for the creation of a democratic and legal state. The development of legislative principles of local self-government in the Ukrainian state is influenced by the experience of Western standards of local self-government, the practice of state building inEastern European and other countries. An important factor for the development of self-government in-stitutions is the process of globalization, which significantly changes socio-political relations, changes the principles of interaction of territorial communities, political organizations and local self-government agencies. The authors of the article study the current theoretical and methodological, legal and practical aspects of local self-government in Ukraine. The historical regularities of the formation and development of local self-government in Ukraine (1991–2019) are studied. The stages of the formation and reform of local self-government and territorial organization of public power in Ukraine are determined, namely the authors have distinguished threestages: 1990-1996 (formation of the institution of local self-government of inde-pendent Ukraine before the adoption of the Constitution); 1996–2014 (development of the Constitutional principles of local self-government); from 2014 to the present day (reform of local self-government of Ukraine, decentralization). The current problems of ensuring the effective functioning of local self-government agencies are studied.

Исследованы актуальные теоретико-методологические, нормативно-правовые и практические аспекты деятельности органов местного самоуправления в Украине. Рассмотрены исторические закономерности его формирования и развития в Украине (1991–2019 годы). Определены этапы реформирования местного самоуправления и территориальной организации публичной власти в Украине. Рассмотрены актуальные проблемы обеспечения эффективного функционирования органов местного самоуправления.
Становление и развитие органов местного самоуправления в Украине (1991–2019 годы)
Formation and development of local self-government agencies in Ukraine (1991–2019)
Keywords: Держава і право. State and Law. Государство и право; місцеве самоврядування; органи місцевого самоврядування; органи публічної влади; децентралізація влади; реформування місцевого самоврядування; євроінтеграція; local self-government; local self-government agencies; public authorities; decentralization of power; local self-government reform; European integration; местное самоуправление; органы местного самоуправления; органы публичной власти; децентрализация власти; реформирование местного самоуправления; евроинтеграция; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина